Diagnosis and management of prefibrotic myelofibrosis. Issue 7 (3rd July 2018) - Rumi, Elisa; Sant'Antonio, Emanuela; Boveri, Emanuela; Pietra, Daniela; Cavalloni, Chiara; Roncoroni, Elisa; Astori, Cesare; Arcaini, Luca
ABSTRACT: Introduction : The 2016 WHO classification comprises two stages of primary myelofibrosis (PMF): early/prefibrotic primary myelofibrosis (pre-PMF) and overt fibrotic PMF (overt PMF). Diagnostic criteria rely on bone marrow morphology, fibrosis grade (0–1 in pre-PMF, 2–3 in overt PMF), and clinical features (leukoerythroblastosis, anemia, leucocytosis, increased lactate dehydrogenase, and palpable splenomegaly). An accurate differentiation from essential thrombocythemia (ET) is pivotal because the two entities show different clinical presentation and outcome, in terms of survival, leukemic evolution, and rates of progression to overt myelofibrosis. Areas covered : The current review provides an overview on how to diagnose and stratify patients with pre-PMF, taking into account their definite and peculiar risk of vascular event, which is often neglected, and their milder disease course, compared with overt PMF, with the aim of improving and individualizing their counseling and management. Expert commentary : Pre-PMF is a new entity characterized by a unique combination of both a thrombo-hemorrhagic risk (that brings it closer to PV and ET) and a definite risk of disease evolution (that places pre-PMF somewhat closer to the overt PMF variant).